Predictive policing and negotiations of (in)formality: exploring the Swiss case - Ajil, Ahmed (International journal of law, crime and justice, 2023)
Predictive policing, that is, the data-driven deployment of police operations on the ground, has become increasingly important in recent years. While predictive policing instruments serve to formalise the ways in which police think and operate, the human agent remains central to their exploitation and translation into strategic, operational, and tactical decision-making. The introduction of predictive policing instruments and methods therefore represents a particularly insightful terrain on which to analyse negotiations of formality and informality. How this plays out in the Swiss context will be addressed in this paper. Based on a review of documents and policies on predictive policing developments and exploratory interviews conducted with police officers and developers, we discuss how institutions and actors engage with predictive policing and what this tells us about the formalisation, respectively informalisation of police work. Our findings point to the challenges related to the federalist organisation of police in Switzerland and the growing importance of cantonal threat management (Bedrohungsmangement) platforms. We also note a general lack of awareness regarding the potentially harmful outcomes of predictive policing instruments, which may be related to a specifically Helvetic narrative that downplays the impact these instruments have on decision-making.